Can genetic testing guide the therapy of cholestatic pruritus? A case of benign recurrent intrahepatic cholestasis type 2 with severe nasobiliary drainage‐refractory itch. Issue 2 (10th January 2018) - Holz, Robert; Kremer, Andreas E.; Lütjohann, Dieter; Wasmuth, Hermann E.; Lammert, Frank; Krawczyk, Marcin
Abstract : Benign recurrent intrahepatic cholestasis (BRIC) is a peculiar familial disease caused by mutations of the genes encoding hepatocanalicular flippase for phosphatidylserine (ATP8B1; BRIC type 1) or the bile salt export pump (ABCB11; BRIC type 2). Here, we report on a patient with nasobiliary drainage‐refractory BRIC type 2 who improved under plasma separation and anion absorption therapy. We also suggest that nasobiliary drainage might be an ineffective approach in carriers of severe loss‐of‐function mutations of the bile salt export pump ABCB11. ( Hepatology Communications 2018;2:152–154)